2018
DOI: 10.1111/ecin.12571
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of Violence and Housing Insecurity

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Insufficient space or privacy, environmental toxins, and housing insecurity are examples of resource-related factors that can affect the quality of social, emotional, and cognitive developmental context insecurity (e.g., Diette & Ribar, 2015) and can contribute to increases in student mobility, childhood stress, and self-regulation challenges (e.g., Herbers, Reynolds, & Chen, 2013;Rumberger, 2003).…”
Section: Familiesmentioning
confidence: 99%
“…Insufficient space or privacy, environmental toxins, and housing insecurity are examples of resource-related factors that can affect the quality of social, emotional, and cognitive developmental context insecurity (e.g., Diette & Ribar, 2015) and can contribute to increases in student mobility, childhood stress, and self-regulation challenges (e.g., Herbers, Reynolds, & Chen, 2013;Rumberger, 2003).…”
Section: Familiesmentioning
confidence: 99%
“…Violence perpetration in this population has received less attention from researchers, but evidence suggests it is linked to prior trauma exposure and associated with a host of maladaptive outcomes, including physical injury, criminal justice system involvement, loss of housing and related social and health services, and loss of peer relationships (Buka et al, 2001;Myers & Oliver, 2008;Singer et al, 1995). While few studies have investigated associations between violence perpetration and housing insecurity in this population, a recent longitudinal analysis indicated that previous violence perpetration predicts both subsequent perpetration and housing instability, suggesting that these are patterned behaviors with bidirectional causal links (Diette & Ribar, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…Adequate housing is also related to the psychological and social well-being of residents [20]. While most of the research on housing insecurity focuses on physical health outcomes, mental health or the psychological benefits of adequate housing, there is some evidence that housing insecurity is associated with crime [17,21,22]. For example, in a qualitative study of women victims, housing instability along with food insecurity were identified as key contributors to intimate partner violence [17].…”
Section: Basic Needs Insecuritiesmentioning
confidence: 99%